(untitled) (Journal of Engineering, 2025)
Polyethylene (PE) waste is both an environmental threat and a chance for innovation in pavement engineering. This review examines low-density (LDPE) and high-density (HDPE) PE as asphalt modifiers, outlining their influence on binder performance, mixture properties, environmental gains, and economic viability. Drawing on laboratory studies and field trials, it compares PE types, dosages, and mixing methods. PE raises the binder’s softening point, viscosity, and elasticity, while reducing penetration and ductility. In mixtures, it can lift Marshall stability by up to 167%, cut rut depth by about 70%, and raise tensile strength by 30%. HDPE usually delivers the bigger mechanical boost thanks to its higher crystallinity, whereas LDPE offers better workability and cold-weather flexibility. Environmentally, PE-modified asphalt can divert up to 2 t of plastic per kilometer, save up to 8% bitumen, and trim greenhouse-gas emissions by 4–7%. Life-cycle analyses indicate 5–15% cost savings through longer service life and lower maintenance. However, key research gaps remain in long-term performance, storage stability, low-temperature cracking, and microplastic risk. Addressing these challenges requires standardized testing and field validation. PE-modified asphalt thus emerges as a practical, scalable, and sustainable option—turning plastic waste into a resilient and cost-effective infrastructure solution.